Internal communication and information integrity. Issue 1 (12th September 2019) - John, Alison
Abstract : Purpose: Internal communication and information integrity – a professional services approach to the impact of "fake news". This paper aims to explain how to build internal communication so that staff can recognise real from fake and the impact that "fake news" can have on organisations through global media. Design/methodology/approach: The author offers a personal perspective of the potential impact of "fake news" on an organisation, and of how internal communication can be built on trust and transparency. Findings: Most effective internal communications are built on the authenticity of the brand. Staff can recognise internal "fake news" and become more adept at recognising other forms of fake news from a global media perspective. Originality/value: This is a personal response to the subject of fake news and information integrity. The paper illustrates an internal communications perspective within a small academic organisation.